PELATIHAN TES KEMAMPUAN AKADEMIK BAGI SISWA SMA KELAS XII UNTUK PERSIAPAN UTBK SBMPTN 2022 - Justin Eduardo Simarmata; Yosepha Patricia Wua Laja; Cecilia Novianti Salsinha; Yohanes Jefrianus Kehi; Agustinus Giovandi Laki; Margareta Rodrigues Gomes; Jeniana Martha Prima Asa; Elinora Naikteas Bano; Yakoba Yusina Muanley; Hendrika Yeni Meti (Jurnal Abdi Insani, 2022)
The Computer-Based Test Exam (UTBK) is a computer-based written test which results are used for the Joint Selection of State Universities (SBMPTN). Based on the results of interviews with the school conducted in January 2022, the preparation of students to face the UTBK 2022 has not been maximized. This happens because there are no facilities as a place for students to practice in preparing the material properly. Besides, students only study routine material according to the textbook, while the UTBK questions are quite different from the material students get in class. The purpose of this activity is to introduce and train strategies in solving the Academic Ability Test (TKA) in preparation for the 2022 UTBK-SBMPTN for high school students Class XII SMA Negeri 1 Kefamenanu. The implementation method in introduction and training activities consists of several stages, including: observation, preparation for introduction and training, implementation of introduction and training, and evaluation of activities. The introduction and training of UTBK TKA questions for Class XII high school students was carried out well. It can be seen from the average student attendance reaching 95.3%. Based on the results of the evaluation of activities before and after the training was given, it was found that the average posttest was higher than the average pretest for each class. The skills and strategies of the trainees in solving the UTBK TKA questions have increased. Based on the results of the pretest and posttest of the training participants, this training activity is successful as a solution to the partner's problem, namely that the preparation of students to face the 2022 UTBK SBMPTN is not optimal.